Tunable blue–green emission properties of Tb3+ doped barium tantalate phosphor - (:unkn) unknown (My University, 2023)
The TTB (tetragonal tungsten bronze) crystal structure with the general formula of A4B2C4M10O30 has three tunnels (A, B, C) of different coordination numbers with a corner-shared octahedral formation. Thanks to these properties, the TTB structure enables various RE ion substitutions and different physical properties to emerge. A series of green-emitting Tb3+ doped barium tantalate phosphors with TTB-type structure between 0.25 and 5 mol% obtained by the solid-state reaction route is reported. The structure of Tb3+ doped TTB–BaTa2O6 was identified by XRD and SEM-EDS analyses. PL relative emission intensity increased from 0.25 to 0.5 mol% and then decreased due to concentration quenching. Depending on the increasing concentration, the colour of the luminescence of BaTa2O6:Tb3+ phosphor can be tuned from blue to green through a cross-relaxation process, where a dipole–dipole energy transfer occurs between two nearby Tb3+ ions. The PL emission of the BaTa2O6:Tb3+ in the CIE diagram tended towards blue to green with the increase in Tb3+ concentration. PL decay profiles of the 5D3 and 5D4 states have a double exponential. The observed lifetimes of the 5D3 state decrease as the decay profiles of the 5D4 state exhibit a stable tendency. Based on the cross-relaxation process, the quantum efficiency (η QE) of the phosphor was evaluated, and the η QE of the 5D3 state with the increase of Tb3+ concentration between 0.25 and 5 mol% varied from 61.63 to 40.85%, respectively.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, COMPOSITES; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; General Materials Science; Physical Sciences; Mechanics of Materials; colour tunable phosphor; decay time; luminescence; Tb3+ doping